Longman dictionary of language teaching and applied linguistics - Richards, Jack C. (Pearson Education Limited, 1992)
This dictionary has been specially written for students of language teaching and applied linguistics. It will be an indispensable resource for those doing course in TEFL, applied linguistics and introductory courses in general linguistics.